The Sacredness and Performativity of Sarafal Anam in the Maulid Celebration: A Living Qur’an Study in Kaloy Village, Aceh Tamiang - Ramadani, Ridha; Damanik, Agusman (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2025)
The Sarafal Anam tradition, performed during the Maulid celebration in Aceh Tamiang, reflects a culturally embedded practice through which Qur’anic values are enacted and transmitted. While often seen as a ceremonial event, this tradition offers deeper significance as a form of lived engagement with sacred texts, particularly within the framework of the Living Qur’an. This study adopts a qualitative descriptive approach, using field observation, in-depth interviews, and document analysis to examine the embodiment of Qur’anic values in the Sarafal Anam tradition. The research was conducted in Kaloy Village, a community known for its consistent preservation of this practice. Thematic analysis was employed with the support of NVivo software to identify key patterns and values expressed through the tradition. Findings reveal that Sarafal Anam functions both as a religious ritual and an educational medium that transmits Qur’anic principles such as prophetic devotion, compassion, social solidarity, and moral responsibility. The practice integrates elements of local culture—regional language, traditional foods, and poetic forms—demonstrating how Islamic values adapt to and are sustained within specific cultural contexts. The tradition plays an important role in character development, especially among the youth, though recent trends show a decline in their active participation. The Sarafal Anam tradition exemplifies the Living Qur’an, offering a meaningful intersection between scripture and culture. To ensure its sustainability, the study recommends youth-centered revitalization efforts, digital adaptation, and institutional support. This research contributes to Qur’anic studies by highlighting how localized rituals serve as dynamic sites for ethical education and cultural continuity in the modern Muslim world.